พฤติกรรมการป้องกันตนเองจากการตกเป็นเหยื่อข่มขืนของวัยรุ่นหญิงในสยามแสควร์ - ลดาวัลย์ รุ่งเรืองพัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To study the causes of beboming rape victims and preventive behavior from becoming rape victims of female teenagers. This research might be used to suggest the measure of preventive behabior from becoming rape victims of female teenagers. The samplings were female teenagers in Siam Square. Seven people were interviewing for detailed information and questionnaires were used collect relevant information from 200 people. The analysis was done by SPSS program. Froms of statistical analysis were percentage, mean, standard deviation, t-teast and one-way anova test. The study found that the level of preventive behavior from becoming rape victims of female teenagers in Siam Square was high. Those female teenagers in Siam Square who stayed at different risk times had no different preventive practices. In short, female teenagers in Siam Square who stayed at different risk places had different preventive methods. Female teenagers who were in desolate places were conscious of preventive manners higher than those who were in their intimate houses. Female teenagers in Siam Square who stay at different risk situations had no different in preventive behavior. Finally, female teenagers in Siam Square who had different knowledge of becoming rape victims were not different in their prevention of rape.